KOMUNIKASI PARTISIPATIF DALAM PEMBENTUKKAN KAMPOENG WISATA BISNIS TEGALWARU (KWBT) DI KECAMATAN CIAMPEA KABUPATEN BOGOR - Khadijah, Siti (Fakultas Komunikasi, Sastra, dan Bahasa, 2014)
Participative communication offersmethods to do the development with the society by involving the local community and understand the local settings. One of the programs, especially economic empowerment involving local communities is the establishment of Kampoeng Wisata Bisnis Tegalwaru (KWBT). Participative communication methods performed by direct dialogue with the whole villagers of Tegalwaru. Ibu Tatiek  not only came to the village but also to villagers who had home industry. The research method used is qualitative method by using descriptive qualitative analysis study.  The unit of analysis is Yayasan Kuntum Indonesia (YKI) in Tegalwaru Kecamatan Ciampea Kabupaten Bogor. The observation unit is the chairman of yayasan Kuntum Indonesia (YKI) and representative of UMKM (micro, small and medium enterprises) who have joined in the Wisata Bisnis Tegalwaru area (KWBT). Kampoeng Wisata Tegalwaru (KWBT) formed in 2011. The idea to establish it initiated by Tatiek Kancaniati through Yayasan Kuntum Indonesia (YKI) as a form of her care and concern as a Tegalwaru villager. She saw the potential and local resources that currently was not optimally empowered and strive looking for solutions to improve Tegalwaru villager who already had a home industry. What have Tatiek done is a form of participation. Principles run by YKI to improve the lives of Tegalwaru rural communities (UMKM) Tegalwaru is equality of status, thus, the nature of the relationship between YKI and the society are paertnership. Participative communication participatory communication process has been carried out to some of the authorities that starts from the pre preparation, preparation until KWBT formed in 2011